1992
DOI: 10.1093/bja/69.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Acute Respiratory Distress in Late Pregnancy

Abstract: Acute severe ventilatory failure from any cause is always a critical emergency. In advanced pregnancy, such an episode is particularly hazardous. The management of a pregnant patient who presented with an acute episode of respiratory distress is described. Although this was though initially to be an asthmatic attack, there was evidence of upper airway obstruction caused by an enlarged thyroid. The major complicating factors and aetiology are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Retrosternal goiter should be taken into account in the differential diagnosis of patients diagnosed as suffering from asthma, and presenting no improvement despite medical therapy. In addition, it should be taken into account that sudden gland enlargement due to hormonal changes might lead to life threatening upper airway obstruction with clinical picture similar to bronchial asthma attack [5]. In a recent very interesting case report, the authors present a case of a pregnant woman in the second trimester who presented with an acute airway obstruction due to the enlargement of a retrosternal goiter [3].…”
Section: Editorialmentioning
confidence: 99%
“…Retrosternal goiter should be taken into account in the differential diagnosis of patients diagnosed as suffering from asthma, and presenting no improvement despite medical therapy. In addition, it should be taken into account that sudden gland enlargement due to hormonal changes might lead to life threatening upper airway obstruction with clinical picture similar to bronchial asthma attack [5]. In a recent very interesting case report, the authors present a case of a pregnant woman in the second trimester who presented with an acute airway obstruction due to the enlargement of a retrosternal goiter [3].…”
Section: Editorialmentioning
confidence: 99%
“…There are several reported cases of urgent thyroid surgery in the pregnant patient to alleviate impending airway obstruction [19][20][21][22]. In 2009, Wittels et al [23] reported a case of immediate postpartum venous engorgement of the thyroid gland giving rise to tracheal compression and airway compromise.…”
Section: Benign Thyroid Disease In Pregnancymentioning
confidence: 99%
“…The ILM is inserted conventionally [2] and an 18 FG Foley catheter introduced through the nose and withdrawn from the mouth using Magill's forceps. A lighted stylet (Trachlight wand™, Laerdal Medical Corporation) is inserted into the bowl and the ILM is manoeuvred until a distinct light is seen at the cricothyroid membrane.…”
mentioning
confidence: 99%